2005
DOI: 10.1111/j.1744-6171.2005.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Skills Training: An Effective Intervention for Internalizing Symptoms in Younger Children?

Abstract: An intervention targeted towards parenting may be efficacious in the treatment of children's internalizing symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 26 publications
1
33
1
1
Order By: Relevance
“…In other words, training the parenting skills help the parents to reduce their children's behavior problems. The results of the present study are consistent with those of Gimpel et al (2002) Previous studies have also shown that unmodified behavioral parenting skills training program-based intervention is effective in reducing the symptoms of the internalizing and externalizing problems of the pre-school children (Cartwright-Hatton et al, 2005). Barrett et al (1996) concluded that after 12 months of the intervention program, 70.3% of the children who received cognitive-behavioral interventions, and 95.6% of the children that their families received the combined cognitive-behavioral intervention and family management training in the treatment group did not show the symptoms of anxiety disorders in the post-test compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, training the parenting skills help the parents to reduce their children's behavior problems. The results of the present study are consistent with those of Gimpel et al (2002) Previous studies have also shown that unmodified behavioral parenting skills training program-based intervention is effective in reducing the symptoms of the internalizing and externalizing problems of the pre-school children (Cartwright-Hatton et al, 2005). Barrett et al (1996) concluded that after 12 months of the intervention program, 70.3% of the children who received cognitive-behavioral interventions, and 95.6% of the children that their families received the combined cognitive-behavioral intervention and family management training in the treatment group did not show the symptoms of anxiety disorders in the post-test compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In the past two decades children's behavioral problems, including externalizing and internalizing have received considerable attention from researchers (Cartwright, Hatton, 2005). Since 1991, Achenbach and his students have conducted many studies using the Children's Behavioral Check List (CBCL) as the instrument to identity children's behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…This would suggest that a broad-based parenting intervention, focussing on gentle, predictable child-management, in addition to anxiety-specific material, might be advantageous. Accordingly, Cartwright-Hatton and colleagues 17 examined the impact of a standard behavioural parent training (BPT) programme on the internalising symptoms of a group of children aged 3-8 years, who, although referred primarily with externalising difficulties, also experienced substantial internalising difficulties. After receiving standard BPT, internalising symptoms reduced significantly, and to the same degree as externalising symptoms.…”
mentioning
confidence: 99%